Perempuan dan Ketahanan Ekonomi Keluarga pada Masyarakat Pesisir Laut Sungsang Kabupaten Banyuasin II Sumatera Selatan - Heri Junaidi (An Nisa'a, 2018)
This study stems from the desire to obtain answers to power relations in building a sakinah family economy. Various role changes occur in the household structure due to the influence of socio-economic culture and development. Patriarchal culture is considered to benefit men and reconstruct the subordination of women, so on matrilinieal kinship system. This inheritance system definitively confers (clan land) exclusively to women with other privileges compared to men. The approach used is the interpretive paradigm that is part of the non-positivistic paradigm. In addition, the study methodology also uses the principle of gender perspective as the focus of analysis. This study also uses a qualitative approach. The subject of this study was determined by a combination of two ways of determining informants in a qualitative study, ie a combination of snowball and accidental. Subjects of research are husband and wife who are in the object area of ​​research with kretaria used by researchers to determine the subject. Data collection techniques are done through observation tools, interviews, and documentation. Technique of analysis with data reduction to get answer of this research. Presented in narrative and descriptive texts, matrices, graphs, and charts. Data analysis is processed into systematic, organized, and structured data.